2009
DOI: 10.1371/journal.pone.0007456
|View full text |Cite
|
Sign up to set email alerts
|

Sumoylation of Transcription Factor Tec1 Regulates Signaling of Mitogen-Activated Protein Kinase Pathways in Yeast

Abstract: Tec1 is a transcription factor in the yeast mitogen-activated protein kinase (MAPK) pathway that controls invasive growth. Previously we reported that a fraction of Tec1 protein is sumoylated on residue lysine 54 in normally growing cells. Here we describe regulation and functional consequences of Tec1 sumoylation. We found that activation of Kss1, the MAPK that directly activates Tec1, results in a decrease in Tec1 sumoylation and a concurrent increase of Tec1 transcriptional activity. Consistent with a role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
(63 reference statements)
0
17
1
Order By: Relevance
“…Although our insulation model may appear to conflict with reports showing that phosphorylation of Kss1 MAPK (and its cognate MAPKK Ste7) occurs even in HOG1 + cells within 15 min after cells are challenged with hyperosmotic KCl (29,30), we believe that our model is compatible with these data. Kss1 phosphorylation occurs slowly, with low abundance, and is transient (detected only at 15 minutes) (30).…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Although our insulation model may appear to conflict with reports showing that phosphorylation of Kss1 MAPK (and its cognate MAPKK Ste7) occurs even in HOG1 + cells within 15 min after cells are challenged with hyperosmotic KCl (29,30), we believe that our model is compatible with these data. Kss1 phosphorylation occurs slowly, with low abundance, and is transient (detected only at 15 minutes) (30).…”
Section: Discussioncontrasting
confidence: 71%
“…Upon detailed analysis of the yeast exposed to both stimuli, we found that toxicity associated with the methods they used may have obfuscated the proper interpretation (see Supplementary Materials). Although the specific substrate(s) on which Hog1 acts to prevent crosstalk remain unknown, there is already support in the literature consistent with an insulation mechanism (30). …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the decline of sumoylated conjugates occurred right after the maximal activation of Hog1, a MAP kinase that is responsible for normal osmo-tolerance in yeast, as detected by anti-phospho-p38 that recognizes dually phosphorylated and thus activated Hog1 ( Fig. 1 , lower panel ) [21], [23]. To determine whether Hog1 has any inhibitory role on the accumulation of sumoylated conjugates induced by hyperosmotic stress, we conducted similar experiment in a hog1Δ mutant.…”
Section: Resultsmentioning
confidence: 97%
“…Failure of Tec1 to be degraded results in cross-talk between the filamentation and mating pathways. Tec1 is subject to complex regulation, being phosphorylated at multiple residues (Bao et al 2010) as well as being sumoylated (Wang et al 2009b). Ste12 itself and other components of the mating/filamentation pathways are also ubiquitinated and degraded to attenuate signaling generated by these pathways (Esch et al 2006).…”
Section: Nutrient-sensing Pathwaysmentioning
confidence: 99%